FACTORS THAT INFLUENCING THE AWARENESS OF THE FIRST ANTENATAL VISIT - Maria Magdalena Awi; Dwi Purwanti; Reny I’tishom; Ninik Darsini (UNIVERSITAS AIRLANGGA, 2020)
ABSTRACTBackground : K1 antenatal care visits at gestational age less than 13 weeks has a very important meaning for pregnant women as well as maternal and child health programs because of their contribution to the prevention of maternal deaths. Coverage of K1 in Puskesmas Watukapu still has a gap of 28.05%.This study aims to determine the factors that influence the K1 antenatal care visit. Methode : The research method was analytic observational with cross sectional design. The sample in this study were all pregnant women trimesters 2 and 3 who came to visit the POLI KIA Puskesmas Watukapu.The sample size of 70 respondents was taken by non-probability sampling technique with consecutive sampling.The independent variable was K1 antenatal care visit, while the dependent variable were age, knowledge, education, parity, attitude, husband's support and family support.Research instrument with questionnaire. Bivariate data analysis used chi square test and multivariate test used multiple logistic regression test. Results:this study found that the proportion of K1 antenatal care visits was 62.4%. Bivariate statistical test results knowledge P = 0,000 (p <0,005), attitude P = 0,135 (P> 0,005), husband support P = 0,000 (P <0,005), family support P = 0,004 (P <0,005), age P = 0,331 (P> 0.005), education P = 0.004 (P <0.005), parity P = 0.015 (P <0.05). Multivariate test results with P value <0.005 was parity with a P value of 0.017.Conclusion: There is a correlation between knowledge, education, parity, husband's support and family support to the awareness of K1 antenatal care visits with the most dominant factor is parity.